Pemberdayaan Santri melalui Pelatihan Kaligrafi dan Pemasaran Kreatif di Pondok Pesantren Al-Falah Pangkah Tegal tahun 2025 - Mochamad Afroni; Aziz Muzayin; Ibni Trisal Adam (Jurnal PKM Merah Putih, 2025)
This community service program focuses on empowering students (santri) of Al-Falah Islamic Boarding School, Pangkah, Tegal, through the integration of Arabic calligraphy training and creative marketing practices. The initiative was designed to enhance both the artistic competence and entrepreneurial awareness of the participants. The methods applied included the identification of educational goals, preparation of instructional materials, practical workshops, evaluation and feedback sessions, and sustained mentoring. The results indicate a notable improvement in artistic quality, marketing literacy, and students’ motivation to develop calligraphy-based economic activities. Beyond skill enhancement, this program has fostered confidence, creativity, and self-reliance among the santri, creating a foundation for sustainable creative industry development within the pesantren environment.